Teachers Reflective Practices and Its Impact on Teaching and Learning English in the Implementation of Merdeka Curriculum - Surdiyantiningsih, Surdiyantiningsih; Hersulastuti, Hersulastuti; Haryono, Purwo; Setyadi, Dwi Bambang Putut; Herawati, Nanik (Journal of English Language and Education, 2025)
The Merdeka Curriculum is a groundbreaking curriculum from the Ministry of Education and Culture of the Republic of Indonesia that aims to further empower all educational units and teachers in developing the potential possessed by students in the current advanced era, which requires competent abilities and skills. The objectives of this research are (1) to describe the reflective teaching practices of the Merdeka Curriculum in English at NW Mataram Junior High School, grade 2, and (2) to explore the impact of teacher reflection on English teaching and learning in the implementation of the Merdeka Curriculum. Using a qualitative case study approach where data is collected from several sources, with the data sources coming from the 8th-grade English teacher, the researcher then conducts direct observations, in-depth interviews with the teacher, and analyzes documents related to the teacher's activities on reflective teaching. This study involves a class and a teacher as participants. Based on the findings (1) English teachers previously used reflective practices to prepare and deliver English teaching to students by assessing previous achievements setting constructive criteria and modifying teaching methods for future success in teaching English. (2) Reflective teaching practices have a significant impact on English teaching and learning, as they can enhance teachers' competencies and teaching quality, optimize students' learning outcomes, and strengthen students' critical and collaborative thinking skills.